Economic valuation of Taman Meragun indigenous territory Sekadau regency, West Kalimantan - Masiun, Stefanus; Tobing, Laurensius (Jurnal Ekonomi, 2024)
A well-prepared abstract enables the reader to identify the basic The Indigenous Dayak Taman Meragun Community, located in the village of Meragun, West Kalimantan, possesses deep-rooted cultural traditions and a sustainable existence. The population of the Taman people totals 2,837 individuals living following ancestral cultural practices. This region reflects the ecosystem of the Bornean tropical rainforest, encompassing hills, lowlands, swamps, and rivers. The Indigenous Dayak Taman Meragun Community sustainably utilizes natural resources, engaging in agriculture, gardening, forestry, and fishing activities in the Taman and Entorap Rivers. However, the designation of the area as a Forest Area and the issuance of palm oil plantation permits jeopardize their access to these resources. These people lead lives deeply intertwined with the customs and laws passed down through generations. The customary forest serves as an economic resource and holds spiritual and ecological significance. Economic potential encompasses agriculture, fisheries, livestock, and forest products. Environmental protection is paramount in the utilization of these potentials. In the face of changing times and threats to their ancestral lands, the Indigenous Dayak Taman Meragun Community endeavours to preserve their cultural identity and practices. They strive for legal recognition of their customary territory while balancing economic needs and environmental preservation. This article delves into the profile of the Taman Meragun customary territory, the challenges it faces, and the efforts made to sustain cultural heritage and the Environment